SIMULASI GLOBAL SYSTEM FOR MOBILE COMMUNICATION ADAPTIVE MULTI RATE SPEECH CODEC - Agoes, Suhartati; Satianingrum, Aulia (Jurnal Teknik Elektro, 2003)
As the wireless technology continuing developing enormously, within it the development ofspeech signal compression joining too, which is implemented in digital communicationsystem. Among the aim is privileged to minimize the channel capacity or bandwidth usageand the speed of transmission. So the use of smaller bits, which brings maximised voicequality, are the most important factor to this technology. One of the speech signalcompression techniques which is implemented in GSM network is called Adaptive Multi Rate(AMR) speech codec or known as GSM-AMR speech codec. There are 8 (eight) bit rates12.2, 10.2, 7.95, 7.40, 6.70, 5.90, 5.15 and 4.75 kbps which is used by GSM-AMR. The bitrates have abilities to adapt to the situation and condition of the network and also ability totailor the operator needs and requirement. The result of a non real-time simulation is shownthat GSM-AMR has a good enough quality of speech signal reconstruction with range ofSNR between 18.78 and 20.35 dB and also range of MSE between 0.053 and 0.079. Thesmaller the bitrate, the better the SNR and the MSE. It was also proven with the comparisonof original signal and constructed signal which is shown that the reconstructed signal hassimilarities figure with the original signal. Overall, the performance of the speech codecgives a good speech quality.Keyword: Speech Codec, GSM-AMR, Adaptive Multi Rate, SNR, MSE.